Explaining Regional and Local Differences in Organic Farming in England and Wales: A Comparison of South West Wales and South East England. Issue 1 (2nd January 2016) - Ilbery, Brian; Kirwan, James; Maye, Damian
Abstract : Ilbery B., Kirwan J. and Maye D. Explaining regional and local differences in organic farming in England and Wales: a comparison of South West Wales and South East England, Regional Studies, Few studies explain the concentration of organic farming in specific regions of England and Wales. This paper compares the development of organic farming in South West Wales and South East England. While the focus in the former is on the use of mainly national marketing channels and the movement of organic produce more than 60 min from the farm, in the latter greater use is made of local and direct marketing channels to distribute organic food within 30 min of the farm. The overriding importance of demand appears to provide a key explanation for regional differentiation in organic farming.